CONCEPTUAL METAPHOR IN THE HEADLINE OF "CHILD ABUSE AND SUICIDE" ON KOMPAS.ID - Soraya, Ratna; Mulyadi, Mulyadi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This research analyzes conceptual metaphors, as popularized by Lakoff and Johnson, which are divided into three types: structural metaphors, ontological metaphors, and orientational metaphors. The focus is on an editorial on Kompas.id titled "Child Bullying and Suicide," using a qualitative research method. The data collection technique involves the listening method, followed by note-taking. The examined data include the editorial text "Child Abuse and Suicide," containing structural metaphors, ontological metaphors, orientational metaphors, source domains, target domains, and image schemas. The research results were recorded and classified based on their categories. The findings reveal six ontological metaphors with image schemas of unity, force, space, and existence; two orientational metaphors with the image schema of space; and two structural metaphors with image schemas of unity and identity. This indicates that ontological metaphors are more commonly used in news writing on the online mass media platform Kompas.id compared to structural and orientational metaphors.